2015
DOI: 10.1080/09297049.2015.1044511
|View full text |Cite
|
Sign up to set email alerts
|

A trial-by-trial analysis reveals more intense physical activity is associated with better cognitive control performance in attention-deficit/hyperactivity disorder

Abstract: Hyperactivity is a key symptom and the most observable manifestation of Attention-Deficit/Hyperactivity Disorder (ADHD). The over-activity associated with ADHD can cause specific challenges in academic settings, extracurricular activities and social relationships. Cognitive control challenges are also well-established in ADHD. The current study included 44 children between the ages of 10 and 17 diagnosed with ADHD or who were typically developing (TD), all of whom had no psychiatric co-morbidity or significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
51
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(62 citation statements)
references
References 22 publications
(26 reference statements)
8
51
2
1
Order By: Relevance
“…The sustained attention and vigilance literature has demonstrated evidence for a decline in attention and performance over time; for example, Helton et al (2005) found a significant decline in attention occurring following about 30 minutes of performing a simulated air traffic control paradigm and Grier et al (2003) found a steady decline in performance over time (measured in 10 minute intervals up to 50 minutes of task time) in their vigilance task. Recent evidence from our laboratory suggests that children with ADHD may increase their levels of activity as a compensatory mechanism to modulate attention and arousal (Hartanto et al, 2016). Therefore longer paradigms may be even more problematic for children with developmental disorders, although this was not supported by significant motion differences in our analysis reported above.…”
Section: Experimental Designcontrasting
confidence: 52%
“…The sustained attention and vigilance literature has demonstrated evidence for a decline in attention and performance over time; for example, Helton et al (2005) found a significant decline in attention occurring following about 30 minutes of performing a simulated air traffic control paradigm and Grier et al (2003) found a steady decline in performance over time (measured in 10 minute intervals up to 50 minutes of task time) in their vigilance task. Recent evidence from our laboratory suggests that children with ADHD may increase their levels of activity as a compensatory mechanism to modulate attention and arousal (Hartanto et al, 2016). Therefore longer paradigms may be even more problematic for children with developmental disorders, although this was not supported by significant motion differences in our analysis reported above.…”
Section: Experimental Designcontrasting
confidence: 52%
“…Hartanto, Kraft, Losif, & Schweitzer (2015) found that students with ADHD were able to concentrate at higher levels when given the opportunity to fidget in the classroom. Results of this study support the use of interventions that enable students to fidget while seated.…”
Section: Foot Fidgetsmentioning
confidence: 99%
“…The sustained attention and vigilance literature has demonstrated evidence for a decline in attention and performance over time; for example, Helton et al (Helton et al, 2005) found a significant decline in attention occurring following about 30 minutes of performing a simulated air traffic control paradigm and Grier (Grier et al, 2003) et al found a steady decline in performance over time (measured in 10 minute intervals up to 50 minutes of task time) in their vigilance task. Recent evidence from our laboratory suggests that children with ADHD may increase their levels of activity as a compensatory mechanism to modulate attention and arousal (Hartanto et al, 2016). Therefore longer paradigms may be even more problematic for children with developmental disorders, although this was not supported by significant motion differences in our analysis reported above.…”
Section: Experimental Designmentioning
confidence: 99%